Applying PBL-Based Student Worksheets In Increasing Students’ Motivation To Learn Mathematics In Class VIII-G SMPN 8 Denpasar In The Academic Year 2023/2024 - Sumandya, I Wayan; Sinta, Ni Putu; Ariana, I Made (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2025)
Schools have used various educational approaches, such as learning models, but students’ motivation to learn mathematics is still low. This study has the following objectives: (1) to find out whether the application of Problem-Based Learning (PBL) student worksheets can increase students’ learning motivation in mathematics, and (2) to find out how students respond to the application of Problem-Based Learning (PBL) student worksheets during the learning process. The research conducted was a class action research (PTK). Students in class VIII G of SMP Negeri 8 Denpasar in the academic year 2023/2024 are the subjects of this research. The focus of the research is how students are motivated to learn and how they respond to the application of Problem-Based Learning (PBL) based student worksheets in learning mathematics. The research was conducted in two cycles, with a cycle consisting of four stages: (1) preparation; (2) action; (3) observation and assessment; and (4) reflection. The report on the results of Classroom Action Research (CAR) shows that the average value of learner motivation in cycle I is 3.35, which is included in the high criteria, while in cycle II it is 3.73, which is included in the high criteria, with an increase of 0.38 and the significance of the increase in motivation. The average learner response score was 52.8, with a standard deviation of 2.26, which showed a positive increase.